Allergenic food as a triggering factor of oral pemphigus vulgaris recurrence - Dewi Puspasari; Irna Sufiawati (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2017)
chronic autoimmune disease with blisters and erosions in the skin and or mucous membranes as its clinical manifestation. The ruptured blisters, followed by erosions and ulcerations, in oral mucous can be painful and interferes the oral function. Spices and seasoning, rich in thiols and isothiocyanates group (garlic, red chillies, black pepper, coriander and cumin seeds), able to trigger the recurrence of pemphigus vulgaris. This case report discussed the allergenic food to tigger the oral lesions in a 49 years old male patient with the diagnosis pemphigus vulgaris who was referred from The Dermatolgy Department. Since about 4 days before admitted to the hospital, the patient complained of painful ulcerations and blisters in the oral cavity that appeared after consuming the spices and seasoning food. Oral lesions caused difficulty in speaking, eating, and drinking, thus led to weight loss. The patient was uncooperative during treatment. Extraoral examination revealed painful erosions and crust on lips which tend to bleed easily. Intraoral examination revealed painful multiple erosions which interfered oral function. The oral lesions showed improvement after being treated using topical corticosteroid, topical antiseptic, antifungal suspension, and multivitamin. Pemphigus vulgaris caused by acantholysis due to autoantibodies IgG against desmogleins 1 and or 3. Tiol and isothiocyanates compound in spices and seasonings of food is one of the triggering factor of recurrence in oral lesions of pemphigus vulgaris